2013
DOI: 10.1371/journal.pone.0057856
|View full text |Cite
|
Sign up to set email alerts
|

Impact of JAK2 V617F Mutation on Hemogram Variation in Patients with Non-Reactive Elevated Platelet Counts

Abstract: BackgroundNon-reactive platelet counts elevation occurs mainly in myeloproliferative disorders (MPDs), which have been reported to be closely associated with JAK2 V617F mutation. Complete blood cell count (CBC) is essential in diagnosis of MPDs, however, the impact of JAK2 V617F mutation on the patients’ hemogram variation remains not clear.MethodsJAK2 V617F mutation was detected by allele specific real-time quantitative fluorescence PCR (AS-qPCR).ResultsOf the 402 non-reactive platelet elevating patients, JAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…Campbell et al [13] [15]. Several studies have shown that the prevalence of the JAK2 V617F mutation in ET is ranging approximately from 23 to 69 % [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In the present study, the frequency of JAK2 V617F mutation positive was 46 % in ET, which is consistent with the studies in the literatures.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Campbell et al [13] [15]. Several studies have shown that the prevalence of the JAK2 V617F mutation in ET is ranging approximately from 23 to 69 % [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In the present study, the frequency of JAK2 V617F mutation positive was 46 % in ET, which is consistent with the studies in the literatures.…”
Section: Discussionsupporting
confidence: 90%
“…Campbell et al [13] [15]. Several studies have shown that the prevalence of the JAK2 V617F mutation in ET is ranging approximately from 23 to 69 % [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, regulation of this process may be disrupted in certain diseases, particularly in neoplasms with a clonal origin (12,(18)(19)(20). It was hypothesized that dysmegakaryocytes reflect disorders of megakaryocyte development and result in dysregulated platelet production, as indicated by higher MPV, P-LCR and PDW values in patients with CML than in healthy controls.…”
Section: B a C B Amentioning
confidence: 99%
“…Recently, the discovery of the JAK2V617F [4], CALR [5], and MPL [6] mutation provided new genetic markers and changed the diagnostic criteria of Ph-negative MPNs. The JAK2V617F mutation, resulting from a single G to T transversion occurs at base position 1849 in exon 14 of the JAK2 gene and leads to a valine to phenylalanine substitution at codon 617, which consequently increases the tyrosine kinase activity, thus resulting in clonal proliferation of one or several myeloid lineages [7] In patients with Ph-negative MPN, cases with a higher JAK2V617F allele burden were thought to have higher hematologic parameters, such as white blood cell counts, hemoglobin values, and platelet counts [8][9][10][11][12]. In addition, accumulating studies about the association between JAK2V617F mutation and vascular events in Ph-negative MPN patients have been reported [13,14] and a higher risk of suffering with vascular events was investigated in patients with JAK2V617F mutation [15,16].…”
Section: Introductionmentioning
confidence: 99%